U-shaped association between serum Klotho and all-cause mortality in US cardiovascular patients: a prospective cohort study - Liu, Shasha; Zhu, Zhanfang; Yu, Kai; Zhang, Wei; Pu, Jie; Lv, Ying; Tang, Zhiguo; Liu, Fuqiang; Sun, Yongqiang (Frontiers in Endocrinology, 2024)
Background: Increased levels of serum Klotho have been associated with a reduced risk of several cardiovascular diseases (CVD). However. Limited studies exist on the association between serum Klotho and mortality in patients with CVD.We collected data from CVD patients in the National Health and Nutrition Examination Survey (NHANES) spanning 2007 to 2016. We linked NHANES data with the National Death Index to determine the survival status of participants.Univariate and multivariable Cox regression models were used to investigate the relationship between serum Klotho levels and mortality in CVD patients. The relationship between serum Klotho quartiles and mortality in CVD patients was visualized using Kaplan-Meier (KM) curves and restricted cubic spine. Finally, subgroup analyses were used to examine the association between serum Klotho and all-cause mortality in different populations.Results: 1905 patients with CVD were finally enrolled in our study with a mean follow-up of 7.1 years. The average age of the participants was 63.4 years, with 58.40% being male. KM showed that lower Klotho levels were associated with lower survival rates. After adjusting for potential confounders, patients with higher serum Klotho levels had lower all-cause mortality (Q1: 1.00, Q2: 0.58 (0.42-0.80), Q3: 0.69 (0.47-1.01), and Q4:0.64 (0.45-0.92). However, the relationship between serum Klotho levels and cardiovascular mortality was not statistically significant. Dose-response analysis shows a U-shaped relationship between serum Klotho levels and all-cause mortality in patients with CVD (P nonlinear=0.002). Subgroup analysis indicated that participants with a history of hypertension had a higher risk of all-cause mortality in serum Klotho Q4 compared to Q1 (P trend <0.05).Conclusion：The relationship between serum Klotho levels and all-cause mortality in CVD patients exhibits a U-shaped association. The underlying mechanisms of this association need further investigation.